Finite element analysis of rock cavern - Chew, Jia Wei (2018)
With the advancement in underground numerical analysis technology, analysis of rock cavern can be easily carried out. This allows studies to be carried out at a faster rate with higher accuracy, thus allowing a better and efficient analysis of it.